1998
DOI: 10.2307/2647648
|View full text |Cite
|
Sign up to set email alerts
|

Civil Society, Political Capital, and Democratization in Central America

Abstract: Robert Putnam argues that civil society-citizen activity in organizations-contributes to successful governance and democracy, which may be very important in the peaceful reconstruction of Central America. Putnam does not, however, specify in detail how civil society might shape government performance. We spell out how citizens' participation in groups might impinge upon the state through both political participation and democratic norms. We consider Putnam's category of "social capital" and add to it new "poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(104 citation statements)
references
References 22 publications
4
95
0
5
Order By: Relevance
“…To avoid duplication of effort, the project steering committee in partnership with interview participants decided to refine the framework and remove this capital from the capacity self-assessment tool. We also acknowledge that a variety of other capitals exist, such as political (Booth andRichard 1998, Lake andHuckfeldt 1998), cultural (Dimaggio and Mohr 1985, Lareau and Weininger 2003, Vryonides 2007, Patterson 2008, and spiritual capitals (Verter 2003). However, rural landholders involved in the development and piloting of the assessment tool believed that human, social, physical, and financial capitals were most pertinent to the delivery of NRM in South Australia at multiple community tiers.…”
Section: Identify Community Capacity Indicators and Scoring Rubrics Bmentioning
confidence: 99%
“…To avoid duplication of effort, the project steering committee in partnership with interview participants decided to refine the framework and remove this capital from the capacity self-assessment tool. We also acknowledge that a variety of other capitals exist, such as political (Booth andRichard 1998, Lake andHuckfeldt 1998), cultural (Dimaggio and Mohr 1985, Lareau and Weininger 2003, Vryonides 2007, Patterson 2008, and spiritual capitals (Verter 2003). However, rural landholders involved in the development and piloting of the assessment tool believed that human, social, physical, and financial capitals were most pertinent to the delivery of NRM in South Australia at multiple community tiers.…”
Section: Identify Community Capacity Indicators and Scoring Rubrics Bmentioning
confidence: 99%
“…A number of studies in Central America have also found a correlation between social capital and political participation (Anderson, 2010;Booth & Richard, 1998;Klesner, 2007). For example, in a 1999 study on the role of organisational involvement in political participation in Central America, Seligson (1999) used survey samples drawn from all the Spanish-speaking countries in South America and revealed a positive correlation between social capital and political participation.…”
Section: Regional Evidencementioning
confidence: 99%
“…The second instance is the creation of a political party. In Honduras, political rather than social capital links formal group activism to democracy in (BOOTH & RICHARD, 1998;Bootha & Richarda, 1999), thus the resistance movement formed a political party and participated in the 2012 primary elections.…”
Section: Conclusion: Building Alternative Opportunity Structuresmentioning
confidence: 99%